AUKUS and Australia’s Threat Perception Towards China - Na'imullah, Muhammad (Jurnal Ilmu Sosial Indonesia (JISI), 2025)
Abstract. This study examines how Australia's participation in the AUKUS agreement reflects a shift in its threat perception toward China. The research aims to: (1) analyze the factors driving Australia's heightened threat perception, and (2) explain why this perception led to the abandonment of its hedging strategy between the U.S. (security ally) and China (economic partner). Methodologically, the article employs a deductive interpretive approach, adapting Rousseau's heuristic model to assess three key dimensions: identity divergence (status-quo vs. revisionist states), military capacity disparity, and China's aggressive regional intentions. The findings reveal that Australia's decision to join AUKUS was primarily motivated by China's revisionist identity, overwhelming military advantage, and assertive actions in strategically vital regions. The study concludes that these factors collectively elevated Australia's threat perception to a level where security concerns outweighed economic benefits, prompting a definitive alignment with the U.S.-led order. Keywords: Australia, China, AUKUS, Threat Perception, Status-quo, Revisionist, Identit. Abstrak. Penelitian ini mengkaji bagaimana partisipasi Australia dalam kesepakatan AUKUS mencerminkan perubahan persepsi ancaman terhadap China. Tujuan penelitian adalah: (1) menganalisis faktor-faktor pemicu peningkatan persepsi ancaman Australia, dan (2) menjelaskan alasan persepsi ini mengakhiri strategi hedging antara Amerika Serikat (sekutu keamanan) dan China (mitra ekonomi). Secara metodologis, artikel menggunakan pendekatan interpretatif deduktif dengan mengadaptasi model heuristik Rousseau untuk menilai tiga dimensi: perbedaan identitas (negara status-quo vs. revisionist), kesenjangan kapasitas militer, dan intensi agresif China di kawasan strategis. Temuan menunjukkan bahwa keputusan Australia bergabung dengan AUKUS terutama dipicu oleh identitas revisionis China, keunggulan militer China, dan tindakan asertifnya di wilayah-wilayah penting. Kesimpulan penelitian menyatakan bahwa faktor-faktor ini secara kolektif meningkatkan persepsi ancaman Australia hingga mengalahkan manfaat ekonomi, mendorong aliansi tegas dengan tatanan pimpinan Amerika Serikat. Kata Kunci: Australia, China, AUKUS, Persepsi Ancaman, Status-quo, Revisionis, Identitas.